Angiotensin II and vascular endothelial growth factor in the vitreous fluid of patients with proliferative diabetic retinopathy. Issue 3 (1st March 2002) - Funatsu, H; Yamashita, H; Nakanishi, Y; Hori, S
Abstract : Aims: To investigate the correlation between the level of angiotensin II and vascular endothelial growth factor (VEGF) in the vitreous fluid and the severity of proliferative diabetic retinopathy (PDR). Methods: During vitreoretinal surgery at the Tokyo Women's Medical University, vitreous fluid samples were obtained from 51 eyes of diabetic patients with PDR, six eyes of diabetic patients without retinopathy, and 16 eyes of non-diabetic patients with ocular disease (controls). The VEGF levels in vitreous fluid and plasma were determined by enzyme linked immunosorbent assay, while angiotensin II levels were measured by radioimmunoassay. Results: The vitreous fluid levels of VEGF and angiotensin II were significantly higher in patients with PDR than in non-diabetic patients or diabetic patients without retinopathy (all p<0.0001). The vitreous fluid level of angiotensin II was significantly correlated with that of VEGF (p<0.0001), and the vitreous concentrations of both VEGF and angiotensin II were significantly higher in patients with active PDR than in those with quiescent PDR (p<0.0001 and p=0.0005, respectively). Conclusion: The authors found that both angiotensin II and VEGF levels were significantly higher in the vitreous fluid of patients with PDR than in that of non-diabetic patients or diabetic patients without retinopathy, and that the levels of both angiotensin II and VEGF were elevated in the active stage of PDR. These findings suggest that angiotensin II contributes to the development and progression of PDR in combination with VEGF.